Effect of Different Formulations of Magnesium Chloride Used As Anesthetic Agents on the Performance of the Isolated Heart of Octopus vulgaris - Pugliese, Chiara; Mazza, Rosa; Andrews, Paul L. R.; Cerra, Maria C.; Fiorito, Graziano; Gattuso, Alfonsina (Frontiers in Physiology, 2016)
Magnesium chloride (MgCl2) is commonly used as a general anaesthetic in cephalopods, but its physiological effects including those at cardiac level are not well characterised. We used an in vitro isolated perfused systemic heart preparation from the common octopus, Octopus vulgaris, to investigate: a) if in vivo exposure to MgCl2 formulations had an effect on cardiac function in vitro and, if so, could this impact recovery from anaesthesia; b) direct effects of MgCl2 formulations on cardiac function. In vitro hearts removed from animals exposed in vivo to 3.5% MgCl2 in sea water (20min) or to a mixture of MgCl2+ethanol (1.12/1%; 20min) showed cardiac function (heart rate, stroke volume, cardiac output) comparable to hearts removed from animals killed under hypothermia. However, 3.5% MgCl2 (1:1, sea water: distilled water, 20min) produced a significant impairment of the Frank-Starling response as did 45min exposure to the MgCl2+ethanol mixture. Perfusion of the isolated heart with MgCl2±ethanol formulations produced a concentration-related bradycardia (and arrest), a decreased stroke volume and cardiac output indicating a direct effect on the heart. The cardiac effects of MgCl2 are discussed in relation to the involvement of magnesium, sodium, chloride and calcium ions, exposure time and osmolality of the formulations and the implications for the use of various formulations of MgCl2 as anaesthetics in octopus. Overall, provided that the in vivo exposure to 3.5% MgCl2 in sea water or to a mixture of MgCl2+ethanol is limited to 20min, residual effects on cardiac function are unlikely to impact post-anaesthetic recovery.